The Impact of Financial Literacy on Saving Behavior in Generation Z in Cirebon City, with Perceived Mobile Banking Service Ease as a Mediating Variable - Rahma Azkia Wardaya (Asian Journal of Management Analytics, 2026)
The purpose of this study is to examine how financial literacy affects Generation Z's saving behaviour in Cirebon City from the perspective of basic mobile banking services as a mediating variable. A quantitative approach with associative study is the research methodology employed. 120 randomly selected respondents made up the research sample. Questionnaires on a five-point Likert scale were distributed in order to collect data. The data was analysed using the Sobel test and multiple linear regression using IBM SPSS Statistics. The study's findings demonstrate that the view of how simple mobile banking services are is positively and significantly impacted by financial literacy. Additionally, saving behaviour is positively and significantly impacted by financial literacy. Additionally, saving behaviour is positively and significantly impacted by the opinion of how simple mobile banking services are.